Fundamental Factors Of Stock Price Assessment In Blue Chip Stock Investment Decisions - Fauzatul Laily Nisa; Cholid Fadil (International Journal of Educational and Life Sciences, 2024)
This research explores the fundamental factors that influence the assessment of blue-chip stock prices and their impact on investment decisions. These factors include net profit, revenue growth, debt ratio, and liquidity. The research method involves analyzing historical financial data of blue-chip companies and surveys of capital market investors. The research results show that net profit and revenue growth have a significant influence on the assessment of blue-chip stock prices. Debt and liquidity ratios have also been shown to have an important impact in shaping investor perceptions. Furthermore, these findings provide a better understanding of how investors use these fundamental factors as a basis for making their investment decisions. The implications of this research contribute to our understanding of the factors that investors should pay attention to when assessing blue-chip stocks. Capital markets practitioners can use this information to design more informed and timely investment strategies. Meanwhile, capital market regulators may consider these findings to increase market transparency and sustainability. Thus, this research not only contributes to the financial literature by exploring the relationship between fundamental factors and stock price valuation, but also provides valuable practical insights for capital market players.